Risk analysis for outpatient experimental infection as a pathway for affordable RSV vaccine development - Siegal, Lisa; Schoevers, J. M. H.; Terstappen, J.; Delemarre, E. M.; Johnston, S. L.; van Beek, L. F.; Bogaert, D.; Chiu, C.; Diavatopoulos, D. A.; Ferreira, D. M.; Gordon, S. B.; Hayden, F. G.; et al. (npj vaccines, 2025)
Controlled human infection models (CHIMs) are an important tool for accelerating clinical development of vaccines. CHIM costs are driven by quarantine facilities but may be reduced by performing CHIM in the outpatient setting. Furthermore, outpatient CHIMs offer benefits beyond costs, such as a participant-friendly approach and increased real-world aspect. We analyze safety, logistic and ethical risks of respiratory syncytial virus (RSV) CHIM in the outpatient setting. A review of the literature identified outpatient CHIMs involving respiratory pathogens. RSV transmission risk was assessed using data from our inpatient and outpatient RSV CHIMs (EudraCT 020-004137-21). Fifty-nine outpatient CHIMs using RSV, Streptococcus pneumoniae, rhinovirus, and an ongoing Bordetella Pertussis outpatient CHIM were included. One transmission event was recorded. In an inpatient RSV CHIM, standard droplet and isolation measures were sufficient to limit RSV transmission and no symptomatic third-party transmission was measured in the first outpatient RSV CHIM. Logistic and ethical advantages support outpatient CHIM adoption. We propose a framework for outpatient RSV CHIM with risk mitigation strategies to enhance affordable vaccine development.
Gesehen am 08.10.2025